Determination of Routes for Daily Newspaper Product Distribution with Saving Matrix Methods. Issue 1 (October 2020) - Adam, N A F P; Sari, I P; Tasya, A; Sutopo, W; Yuniaristanto,
Abstract: The newspaper industry has several distinctive characteristics that make it stand out from other industries due to tight production and delivery times. The results of a case study in one of the newspaper companies in the city of Surakarta, found several problems, one of which is the slow distribution process due to the determination of the wrong route. The problem of distribution is the problem of the Vehicle Routing Problem (VRP). Vehicle Routing Problem is a problem related to determining the optimal distribution route by involving several obstacles to serve a number of agents at the request of each agent. One of the obstacles of the Vehicle Routing Poblem is the capacity of the vehicle. This study applies the Vehicle Routing Problem using the Nearest Neighbor method to optimize the distribution route. The Nearest Neighbor method is used to design routes based on the next closest distance. Distribution efficiency is evaluated based on the total distance, time and load borne by the vehicle fleet. The results showed that the distribution route was divided into two routes with a total distance traveled as far as 27.3 km and a total time of 1 hour 30 minutes in accordance with the time windows policy that is applied daily Solopos. Based on the use of these methods, it can save company expenses of Rp. 134, 160.00 per day or Rp. 1, 609, 920.00 per month in product distribution for the Surakarta City area.